(untitled) - Luo, Yiqi (Amsterdam, 2006)
This book synthesizes the already published research findings and presents the fundamentals of this subject. Including information on global carbon cycling, climate changes, ecosystem productivity, crop production, and soil fertility, this book will be of interest to scientists, researchers, and students across many disciplines
Keywords: Soil aeration,Quản lý đất đai,Khí Carbonic,Atmospheric carbon dioxide,Soil management,Soil air; Environmental aspects,khía cạnh môi trường,Khía cạnh môi trường,Environmental aspects.,Environmental aspects.,Environmental aspects